Transformation of the Archetype: A Return to Fairy Tale - Zhanysbekova, Elmira; Uskenbayeva, Rauza; Kydyrbayeva, Nazym (Journal of Ecohumanism, 2024)
The paper is devoted to the study of archetypal images in the genre of literary fairy tales. Any author’s work has a certain set of archetypal images that have their own special national meaning. Each image has its own specific functions that embody artistic, emotional, psychological, social and philosophical tasks. These tasks form the author’s final vision when choosing a particular image. One of such bright and frequent images in folklore studies, which transferred to the literary fairy tale is the image of a young neophyte, a boy or a girl. A boy often personified in the image of a bald - Tazsha, which has been successfully transformed into the genre of a literary fairy tale. In the same way, the images of animals, which are the first characters in fairy tales as a whole, and the analogue of their visions have often been and still are indicative. Also, the article discusses the genre features of the folklore fairy tale, which have preserved and left their mark on modern fairy tale texts. The author’s thinking operates with the collective consciousness, reflected in archetypal images and motifs, and the consciousness of the reader, reflecting cognitive dissonance. The methodology of the research involves the continuity of scientific approaches, as well as the use of traditional and innovative methods of literary analysis: content analysis, comparative typological method, mythopoetics and psychoanalysis.